Civil liability of genetic research - Mohammad Norozian; Salman Valizadeh; Farhad Edrisi (مطالعات فقه و حقوق اسلامی, 2023)
Human advances have led to evolution of different sciences, which has consequently promoted their interrelationships. Genetics is not an exception and has played a significant role in legal issues related to humans, e.g., civil liability of genetic research. As not all new research methods can lead to certain positive results, i.e., they may cause serious harm to humans, it assumes added importance to investigate different genetic principles and methods related to compensation as well as the extent of each party’s tortious and contractual liability. However, the research participant may not have a disease and only decide to voluntarily participate in the study for either benevolent or research purposes. Therefore, it is essential that governments and other responsible bodies provide optimal conditions so that physical and spiritual harms inflicted on participants could be compensated by insurance companies or other funding agencies. Meanwhile, scientific research is necessary for the advancement of science in human societies, and the government and the legislator should provide essential conditions for such research while making sure that the rights of the patients and research participants are observed.